2015
DOI: 10.11118/actaun201563020499
|View full text |Cite
|
Sign up to set email alerts
|

The Main Factors Influencing the Destination Choice, Satisfaction and the Loyalty of Ski Resorts Customers in the Context of Different Research Approaches

Abstract: The paper summarizes scientifi c approaches to researches in the fi eld of destination choice, satisfaction and the loyalty of ski resorts customers. Information about existing models and trends from scientifi c journals are analysed. Multiattribute models are widely used in researches dealing with satisfaction and loyalty. It can be presumed that tourist overall satisfaction is determined by destination image and attribute satisfaction. Tourist attribute satisfaction is also directly infl uenced by destinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Their results showed that tourist satisfaction is directly influenced by the image of the destination; and that, in turn, destination loyalty is influenced by overall satisfaction [27]. Another study used the factor-cluster method to identify six different customer segments [28].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that tourist satisfaction is directly influenced by the image of the destination; and that, in turn, destination loyalty is influenced by overall satisfaction [27]. Another study used the factor-cluster method to identify six different customer segments [28].…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that these variables may also be important for some visitors of a ski resort, but likely they are not that important for all visitors and not directly related to the actual skiing experience for the entire ski resort's visitor base. At the same time, as the actual ski experience is a multi-dimensional experience, it is affected by issues like the variety, length and quality of ski slopes, capacity of the ski lifts, length of ski runs, speed of access to the ski lifts and number of slopes (Alexandris et al, 2006;B ediov a and Ryglov a, 2015;Kyle et al, 2010;Matzler et al, 2007). Therefore, these variables will be used as service quality skiing indicator variables in this study.…”
Section: Service Quality Skiingmentioning
confidence: 99%
“…Moreover, accessibility is a vital prerequisite at any tourist destination [29]. Based on the comparison of the results of the studies, the main factor influencing the choice of location and destination are travel distance and climatic factors (e.g., snow conditions, ski slopes) [30]. With climate change, the appeal of snow-safe destinations is strongly influenced by price and travel time [31].…”
Section: Factors That Influence the Distribution Of Ski Resortsmentioning
confidence: 99%